Long non-coding RNA TINCR promotes hepatocellular carcinoma proliferation and invasion via STAT3 signaling by direct interacting with T-cell protein tyrosine phosphatase (TCPTP). Issue 1 (1st January 2021) - Tang, Chengwu; Feng, Wenming; Bao, Ying; Du, Huimin
ABSTRACT: The long non-coding RNAs (lncRNAs) participate in modulating numerous important cancer phenotypes via formation of RNA-protein complex. TINCR (terminal differentiation-induced lncRNA) modulates cancer cell behavior in many human malignancies, such as hepatocellular carcinoma (HCC). Herein, we proposed to investigate the underlying mechanism by which TINCR regulates HCC progression via formation of RNA-protein. RNA pulldown, LC-MS/MS, bioinformatics analysis, and RNA immunoprecipitation (RIP) assays were employed to identify TINCR-interacting protein TCPTP in HCC cells. The siRNAs for TINCR and TCPTP were transfected into HCC cells. The plasmids encoding full length or the 1–360 nt deletion of TINCR were generated and applied to cell transfection. The CCK-8, colony formation, EdU, wound healing along with transwell assays were employed to examine cell proliferation, apoptosis, migration, and infiltration. Real-time PCR, as well as western blot assays were employed to assess the levels of STAT3 phosphorylation and its target genes. We identified 1–360 nt region of TINCR, which directly bound with the phosphatase domain of TCPTP to inhibit its tyrosine phosphatase activity. Then, the results showed that the increasing of cell growth, migration, infiltration, and the reducing of apoptosis in TINCR-knockdown HCC cells was remarkably reversed with TCPTP silence. Additionally, Δ1-360 TINCR overexpression did not affect HCC cell growth, apoptosis, migration, infiltration, and STAT3 target genes expression. Our data revealed that TINCR directly bound TCPTP and suppressed the dephosphorylation of STAT3, thus promoting STAT3 activation and its downstream target genes in HCC progression and tumorigenicity. Highlights LncRNA TINCR interacted with protein TCPTP LncRNA TINCR maintained STAT3 phosphorylation LncRNA TINCR affected STAT3 signaling in HCC Abbreviations: lncRNAs: long non-coding RNAs; TINCR: terminal differentiation-induced lncRNA; TCPTP: T cell protein tyrosine phosphatase; siRNA: small-interfering RNA; HCC: hepatocellular carcinoma; nt: nucleotide; LC-MS/MS: Liquid Chromatography - Tandem Mass Spectrometry; RIP: RNA immunoprecipitation; ANOVA: analysis of variance; EdU: 5-ethynyl-2'-deoxyuridine; real-time PCR: real-time polymerase chain reaction; CCK-8: cell counting kit-8; aa: amino acids; STAT3: signal transducer and activator of transcription 3 Graphical abstract: